2017
DOI: 10.1007/s10803-017-3277-z
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Boys Diagnosed with Autism Spectrum Disorder: A Case-Control Study

Abstract: This study compared bone mineral density (BMD) of the spine obtained by dual-energy X-ray absorptiometry (DEXA), nutritional status, biochemical markers, and gastrointestinal (GI) symptoms in 4-8 year old boys with Autism Spectrum Disorder (ASD) with a group of age-matched, healthy boys without ASD. Boys with ASD had significantly lower spine BMD compared to controls but this was not correlated with any biochemical markers, dietary intake of calcium and vitamin D, elimination diet status, or GI symptomology. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The GSRS has been used in several studies of children with ASD [49] but the language used is complicated and overly clinical, and it was originally designed for use in adults to screen for irritable bowel syndrome and peptic ulcer disease [42]. However, at the time of study initiation, the GSRS was considered the best questionnaire available for capturing the anticipated five domains in GI symptomatology: abdominal pain, reflux, indigestion, diarrhea, and constipation and has since been used in a number of ASD studies [50][51][52][53]. Overall, GI symptoms improved over time in most of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The GSRS has been used in several studies of children with ASD [49] but the language used is complicated and overly clinical, and it was originally designed for use in adults to screen for irritable bowel syndrome and peptic ulcer disease [42]. However, at the time of study initiation, the GSRS was considered the best questionnaire available for capturing the anticipated five domains in GI symptomatology: abdominal pain, reflux, indigestion, diarrhea, and constipation and has since been used in a number of ASD studies [50][51][52][53]. Overall, GI symptoms improved over time in most of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Barnhill et al examined the bone mineral density of the lumbar spine by dual-energy X-ray absorptiometry in a cohort of boys with and without ASD, at the same age range as the previous paper. They found that a significantly lower bone mineral density in boys with ASD compared to the controls can be identified in 4-8-year-old children, while the nutrient intake seemed not to be associated with this effect [114].…”
Section: Evidence From Other Neurodevelopmental Disabilitiesmentioning
confidence: 97%